American Prints Today : 1962. - Museum of Fine Arts, Boston; The Art Institute of Chicago (New York : Print Council of America, 1962)
Albers, Josef ; Altmann, Harold ; Baskin, Leonard ; Becker, Fred ; Blaustein, Al ; Bunce, Louis ; Casarella, Edmond ; Crawford, Ralston ; Day, Worden ; Dehn Adolf ; Deshaies, Arthur ; Durieux, Caroline ; Edmondson, Leonard ; Forsberg, Jim ; Frasconi, Antonio ; Glarner, Fritz ; Hartigan, Grace ; Johns, Jasper ; etc.
American Prints Today : 1962, Museum of Fine Arts, Boston, September 20 - October 21, 1962 / The Art Institute of Chicago, September 21 - October 21, 1962 / etc.
boek